Analisis Keamanan Dan Eksploitasi Kernel Android 13 Menggunakan Metasploit Reverse_Tcp - Alhidamkara, Salman; Somantri, S; Kharisma, Ivana Lucia (LPPM STIKOM Tunas Bangsa, 2024)
The development of information technology, especially in the mobile field, has changed the way we interact with devices substantially. Android, as the most dominant mobile operating system used worldwide, attracts significant attention to its security aspects. Despite improvements in the security of Android devices, exploitation attempts continue to be made by security researchers and hackers using various methods, including exploitation via Reverse_TCP with tools such as Metasploit. This research aims to analyze the security of Android 13 devices using the Reverse_TCP method via Metasploit. The methods used involve exploitation by sending backdoor applications, opening Meterpreter sessions, and stealing data such as SMS and call logs. The results showed that Google Play Protect detected malicious applications, but the applications could still be installed and run, indicating a weakness in the security detection system. Reverse_TCP exploits can lead to unauthorized access to personal data and full control of the device, posing significant risks to users. Proposed preventive measures include using the Mobile Security Framework (MobSF), enabling Google Play Protect, and disabling unnecessary app permissions. This study suggests further research to overcome limitations and explore further the security aspects of Android